Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA dengan Menggunakan Metode Eksperimen Di SD Negeri 04 Birugo - Susanti, Desi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research the writer applied metode eksperimen is learning processes for there are many student. Observational stage is described in planning , implementation, and reflection stages. Type of this research is classroom action research, using both  qualitative appr and quantitative apprauching  one consisting of two cycles. Observational student is class fou rgreat and observational. Analysis’s result to learning planning on.Cycle is 73,4 experience step-ups on the second cycle, by derived 90,5. Result observinging to activity learns in learning on I, cycle is 68,7,1 experience step-us on the second is 81,4. Result observinging to student activity in learning on I cycle is 68,7 experience step-ups on the second cycle, by derived 82,5. Learning  result the student perform research average 71,8 on the second cycle, average 79,9. In short, the classroom action research uses metode eksperimen could increase the student’s study result for exact science course. Kata kunci : hasil belajar, IPA, metode, pembelajaran, dan eksperimen